Seismic behavior of steel reinforced concrete cross-shaped columns after exposure to high temperatures. (1st March 2021) - Wang, Yuzhuo; Xu, Tiangui; Liu, Ziqing; Li, Guoqiang; Jiang, Jian
Highlights: Post-fire tests on four cross-shaped steel reinforced concrete columns are conducted. A formula to calculate the post-fire shear capacity is proposed. The specimens exhibit flexural failure mode after high temperatures. The post-fire seismic behavior is governed by reinforced section steel. The post-fire seismic behavior is reduced by 50% for maximum temperature of 800 °C. Abstract: This paper experimentally and analytically studies the seismic behavior of cross-shaped steel reinforced concrete (SRC) columns after exposure to high temperatures. A total of four SRC cross-shaped column specimens are heated at a constant maximum temperature of 600 °C for different heating durations (0 min, 60 min, 120 min and 180 min), and are tested under cyclic loading until failure after cooling down to ambient temperature. The hysteresis curve, skeleton curve, ductility, stiffness degradation and energy dissipation capacity of the specimens are analyzed. The experimental results show that the SRC cross-shaped columns exhibit a flexural failure mode after exposure to elevated temperatures, and their post-high temperature seismic behavior is governed by the embedded section steel. The heating duration greatly affects the post-high temperature cracking load of SRC cross-shaped columns (up to 67%) due to the damaged bonding condition between section steel and concrete during heating. A good post-high temperature energy dissipation capacity is achieved due to the improved ductility and recovered strength of section steel. The improvement in ductility reaches about 16%, 22% and 31% of the initial value for a heating duration of 60 min, 120 min, 180 min at 600 °C, respectively. Heat transfer analyses considering a wide range of maximum temperatures up to 1000 °C are conducted using validated numerical models. A formula to calculate the shear capacity of SRC cross-shaped columns after exposure to high temperatures is proposed. It is found that the post-high temperature shear capacity is greatly affected by maximum temperatures but is not sensitive to heating duration. The contribution of section steel to shear capacity increases as temperatures increase, by a range of 38% to 68% for maximum temperatures from 200 °C to 900 °C. A reduction factor of 90%, 80%, 65%, 50% and 40% can be conservatively used for practical design for maximum exposure temperatures of 200 °C, 400 °C, 600 °C, 800 °C, 1000 °C, respectively.